A new species of the genus Peltogaster Rathke, 1842 (Cirripedia: Rhizocephala: Peltogastridae) parasitizing the hermit crab Pagurixus boninensis (Melin, 1939) from the Bonin Islands, Japan - Yoshida, Ryuta; Naruse, Tohru (Zootaxa, 2016)
A new rhizocephalan species, Peltogaster unigibba n. sp., is described from the host hermit crab, Pagurixus boninensis (Melin, 1939), from the Bonin Islands, Japan. Of the16 known species of Peltogaster now currently recognised, P. unigibba n. sp., and P. contorta Boschma, 1958 share a left lobe that projects beyond the mantle aperture. The two species can be distinguished from one another by the position of the opening of the mantle aperture. The new species most closely resembles P. naushonensis Reinhard, 1946 in its internal structure, but clearly differs in the relative length of the colleteric glands. Peltogaster unigibba n. sp. represents the first record of a rhizocephalan from the oceanic Bonin Islands, and the second record of a rhizocephalan from an oceanic island in the northern hemisphere.